SEED VIABILITY, GERMINATION, AND SEEDLING GROWTH OF CAPSICUM CULTIVATED SPECIES - Corozo Quiñónez, Liliana; López-Cedeño, Johanna; Lascano-Borja, Gabriela; Monteros-Altamirano, Álvaro; Arteaga-Alcívar, Francisco; Jaimez, Ramón E.; Pinoargote, Miryan; Cedeño-García, George; Sánchez-Mora, Fernando; Celi-Soto, Adriana; García-Dávila, Mario Augusto (Chilean Journal of Agricultural & Animal Sciences, 2023)
Seed viability of domesticated and cultivated Capsicum species: Capsicum annuum L., Capsicum baccatum L., Capsicum chinense Jacq., Capsicum frutescens L., and Capsicum pubescens Ruiz & Pav. was tested by the tetrazolium method. The seeds were soaked in three tetrazolium salt solutions of 1, 0.5 and 0.2%, and temperature conditions of 30 - 35 °C for 3 h. The percentage of seeds stained in relation to the total number of seeds was evaluated. To estimate germination, the seeds were subjected to chemical treatments with gibberellic acid (GA3) at doses of 0, 100, 200, 300, and 400 mg L-1 at room temperature for 24 h. The germination rate was estimated, while plant height was evaluated at 10, 20 and, 30 days after sowing (DAS). Capsicum seed viability fluctuated between 52.44% and 97.11%. The highest percentage of viability was obtained with the 1% dose of tetrazolium (81.63%), while the 0.2% dose resulted in the lowest average value (63.7%). In addition, C. annuum, C. baccatum and C. chinense showed high staining patterns, while most of the observed patterns in C. frutescens corresponded to non-viable seeds. After GA3 application, average seed germination was 100% in C. chinense; 75.6% in C. baccatum; 73.32% in C. annuum; and 61.5% in C. frutescens. However, the application of GA3 did not cause an additional effect on the germination of Capsicum seeds. The highest plant height at 30 DAS was observed in accessions of C. annuum (9.08 cm), while C. chinense presented the lowest value (4.49 cm).